2001
DOI: 10.1177/0734242x0101900506
|View full text |Cite
|
Sign up to set email alerts
|

Solid waste characterisation study in the Guadalajara Metropolitan Zone, Mexico

Abstract: The key findings of a solid waste characterisation study conducted at the Guadalajara Metropolitan Zone, Mexico, are reported. Objectives of the study were to estimate the daily generation rate of household (HSW) and municipal solid waste (MSW), characterise and compare their composition by type of material, determine the proportion that HSW contributes to MSW, explore changes in MSW composition through time after final disposal, and estimate the types and amount of MSW that are sorted out for recycling at fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 16 publications
3
41
0
1
Order By: Relevance
“…Research carried out in several places around Mexico show that, indeed, the organic composition of food scraps and yard trimmings is lower in the north border region. For example, the results published by BernachePérez et al [26] in Guadalajara show food scraps at 40.7%, yard trimmings at 12.2%, paper at 10%, and plastics at 9%. On the other hand, Buenrostro [25] reports that food scraps in Morelia accounted for 50.95%, paper 7.62% and plastics 7.68%.…”
Section: Composition Of Mswmentioning
confidence: 99%
See 2 more Smart Citations
“…Research carried out in several places around Mexico show that, indeed, the organic composition of food scraps and yard trimmings is lower in the north border region. For example, the results published by BernachePérez et al [26] in Guadalajara show food scraps at 40.7%, yard trimmings at 12.2%, paper at 10%, and plastics at 9%. On the other hand, Buenrostro [25] reports that food scraps in Morelia accounted for 50.95%, paper 7.62% and plastics 7.68%.…”
Section: Composition Of Mswmentioning
confidence: 99%
“…Lower figures are shown by Gómez et al [24] in Chihuahua with 0.676 kg per person per day, Bernache-Pérez et al [26] in Guadalajara with 0.580 kg per person per day, and Buenrostro [25] in Morelia with 0.629 kg per person per day. Compared to other cities worldwide, it can be observed that daily per capita generation in Ensenada is similar to the generation rates described by Hristovski et al [40] with 1.06 ± 0.56 kg in Veles, Macedonia (developing economy); Bernache-Pérez et al [26], who states that developed countries such as Japan generates 1.22 kg per person per day and Germany 1.15 kg per person per day; and Gomes et al [36], who states that Portugal generates 1.2 kg per person per day. This is in contrast to other developed countries such as the United States with a daily per capita generation of 1.98 kg per person per day and Canada with 1.64 kg, countries where a stressed difference may be noted.…”
Section: Daily Per Capita Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Un método que permite estimar la cantidad de residuos que producen las localidades urbanas y rurales, así como cuantificar el equipamiento nece sario (camiones recolectores y contenedores) y diseñar las obras de ingeniería (rellenos sanitarios y plantas de separación), son los llamados estudios de generación y cuantificación de subproductos de los RSU (Bernache et al 2001, Al-Jarallah y Aleisa 2014).…”
Section: Introductionunclassified
“…Many previous studies have examined household solid waste (HSW) generation and physical waste composition. Berneche-Perez [4], Ojeda-Benitez et al [5], Alhumoud et al [6], and Gómez et al [7] analyzed HSW to identify the waste generation rate and the potential for using recyclable wastes. However, the HSW generation rates and compositions were found to differ among communities.…”
Section: Introductionmentioning
confidence: 99%